“The Role of Islamic Religious Institutions in Strengthening the Religious Identity of Muslim Youth in Canada: An Analytical and Research-Based Study” (Contemporary Journal of Social Science Review, 2025)
Islamic religious institutions in Canada play a central role in shaping the religious identity of Muslim youth, offering guidance, education, and communal support within a multicultural and secular context. This research-based analytical study examines the mechanisms through which mosques, Islamic centres, Islamic schools, and university chaplaincies influence youth religious development, highlighting both opportunities and challenges. The study identifies key strategies employed by these institutions, including structured religious education, mentorship programs, youth engagement activities, ritual participation, and safe spaces for dialogue. These mechanisms collectively foster cognitive, emotional, and ethical development, enabling young Muslims to internalize Islamic teachings while navigating the complexities of Canadian society.The study also evaluates institutional challenges, such as generational gaps, limited professionalization, resource constraints, curriculum relevance, inclusivity, and digital engagement. Best practices adopted by institutions including interactive pedagogy, youth-centered programming, professional staff development, digital outreach, community service, and interfaith collaboration are shown to enhance the effectiveness of identity formation efforts. Impact assessment reveals that youth participating in these programs exhibit higher religious literacy, consistent ritual observance, leadership skills, community engagement, and confidence in reconciling religious and Canadian identities.Policy implications emphasize the need for targeted support, including funding, staff training, curriculum innovation, youth participation, inclusivity, and digital integration. The findings underscore that sustainable, adaptive, and inclusive strategies are essential to ensure that Islamic institutions continue to nurture resilient, informed, and socially responsible youth. The study concludes that Islamic religious institutions serve as vital platforms for holistic identity development, enabling Canadian Muslim youth to cultivate a strong sense of faith while actively participating in the broader multicultural society.